The Acrocallosal Syndrome in A Neonate With Further Widening of Phenotypic Expression - SINGHAL*, Ravish; PANDIT, Sadbhavna; Saini, Ashok; SINGH, Paramjit; DHAWAN, Neeraj (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Singhal R, Pandit S, Saini A, Singh P, Dhawan N. The Acrocallosal Syndrome in A Neonate With Further Widening of Phenotypic Expression. Iran J Child Neurol. 2014 Spring;8(2):60-64. The presentation of the typical characteristics of the acrocallosal syndrome (ACLS) are hypoplasia/agenesis of corpus callosum, moderate to severe mental retardation, characteristic craniofacial abnormalities, distinctive digital malformation, and growth retardation in a neonate. An Indian neonate presented on day 1 of life (youngest in the literature to be reported) with combination of abnormalities consistent with the acrocallosal syndrome and some additional findings. The baby, born to non-consanguineous, healthy parents, presented with macrocephaly, prominent forehead, hypertelorism, polydactyly of the hands and feet, duplication of hallux, hypotonia, recurrent cyanotic episodes, rib anomalies, dextro-positioning of heart, and delayed fall of umbilical cord. As the mode of inheritance of ACLS is autosomal recessive, the risk of recurrence is 25%. Genetic counselling is of prime importance, Polydactyly, and central nervous system malformations can be detected by ultrasonography in the second trimester, but due to variability of presentation, prenatal diagnosis may not always be possible. References 1. Schinzel A. Postaxial polydactyly, hallux duplication, absence of corpus callosum, macencephaly and severe mental retardation: a new syndrome? Helv Paediatr Acta 1979:34:141-146. 2. Schinzel A. The acrocallosal syndrome: expansion of the phenotypic spectrum. Clin Dysmorphol 1994;3:31-34. 3. Schinzel A, Schmid W. Hallux duplication, postaxial Polydactyly, absence of corpus callosum, severe mental retardation and additional anomalies in two unrelated patients: a new syndrome. Am J Med Genet 1980;6:241-249. 4. Moeschler JB, Pober BR, Holmes LB, Graham JM Jr. Acrocallosal syndrome: new findings. Am J Med Genet 1989;32:195-199. 5. Schinzel A, Kaufmann U. The acrocallosal syndrome in sisters. Clin Genet 1986;30:399-405. 6. Koenig R, Bach A, Woelki U, Grzeschik KH, Fusch S. Spectrum of acrocallosal syndrome. Am J Med Genet 2002;108:7-11. 7. Schinzel A. The acrocallosal syndrome in first cousins: widening of the spectrum of clinical features and further support for automal inheritance. J Med Genet 1988;25:332-336. 8. Hendriks HJE, Brunner HG, Haagen TAM, Hamel BCJ. Acrocallosal syndrome. Am J Med Genet 1990;35:443-446. 9. Yuksel M, Caliskan M, Ogur G, Ozmen M, Dolunary G, Apak S. The acrocallosal syndrome in a Turkish Boy. J Med Genet 1990;27:48-49. 10. Casamassima AC, Beneck D, Gewitz MH, Horowitz MA, Woolf PK, Pettersen IM, Shapiro LR. Acrocallosal Syndrome: additional manifestation. Am J Med Genet 1989;32:311-317. 11. Courtens W, Vamos E, Christophe C, Schinzel A. Acrocallosal syndrome in an Algerian boy born to consanguineous parents: review of the literature and further delineation of the syndrome. Am J Med Genet 1997;69:17-22. 12. Bassam R Ali, Jennifer L Silhavy, Nadia A Akawi, Joseph G Gleeson Lihadh Al-Gazali. A mutation in KIF7 is responsible for te autosomal recessive syndrome of macrocephaly, multiple epiphyseal dysplasia and distinctive facial appearance. Orphanet J Rare Dis 2012 May 15;7:27.